The “WWHow” Concept for Prospective Categorization of Post-operative Severity Assessment in Mice and Rats - Tappe-Theodor, Anke; Pitzer, Claudia; Lewejohann, Lars; Jirkof, Paulin; Siegeler, Katja; Segelcke, Astra; Drude, Natascha; Pradier, Bruno; Pogatzki-Zahn, Esther; Hollinderbäumer, Britta; Segelcke, Daniel (Frontiers in Veterinary Science, 2022)
The prospective severity assessment in animal experiments in the categories' non-recovery, mild, moderate, and severe is part of each approval process and serves to estimate the harm/benefit. Harms are essential for evaluating ethical justifiability, and on the other hand, they may represent confounders and effect modifiers within an experiment. Catalogs and guidelines provide a way to assess the experimental severity prospectively but are limited in adaptation due to their nature of representing particular examples without clear explanations of the assessment strategies. To provide more flexibility for current and future practices, we developed the modular Where-What-How (WWHow) concept, which applies findings from pre-clinical studies using surgical-induced pain models in mice and rats to provide a prospective severity assessment. The WWHow concept integrates intra-operative characteristics for predicting the maximum expected severity of surgical procedures. The assessed severity categorization is mainly congruent with examples in established catalogs; however, because the WWHow concept is based on anatomical location, detailed analysis of the tissue trauma and other intra-operative characteristics, it enables refinement actions, provides the basis for a fact-based dialogue with authority officials and other stakeholders, and helps to identify confounder factors of study findings.